"Nuclear rights, nuclear wrongs / edited by Ellen Frankel Paul...[et al]" - "Paul, Ellen Frankel (ed.)" (England, 1986)
Nuclear war is a terrifying prospect. The bomb has haunted us and conferented us with a hosr of questions that test the limits of our objective. This volume adds much needed perspective to the controversy by emaning in a rational and objective way the basic moral question. this book is emphasized on this question. bomb?
Keywords: Peace